(untitled) (American Journal of Technology and Applied Sciences, 2025)
The article examines the quality management systems of healthcare services and the compliance of service quality and safety indicators with international requirements. Based on the content of the ISO 7101:2023 and ISO 9001:2015 standards, in essence, the new standard expands the requirements of ISO 9001 and defines them in connection with the specifics of healthcare organizations. ISO 7101 pays great attention to the involvement of patients and their representatives in the treatment process. It is based on the fact that the concept of leadership is effectively expanded from leadership in healthcare organization employees to leadership in patients and society.